Levamisole in Illicit Trafficking Cocaine Seized: A One-Year Study. Issue 5 (20th October 2017) - Martello, Simona; Pieri, Massimo; Ialongo, Cristiano; Pignalosa, Stefano; Noce, Gianluca; Vernich, Francesca; Russo, Carmelo; Mineo, Federico; Bernardini, Sergio; Marsella, Luigi Tonino
ABSTRACT: Cocaine use is increasing around the world and its purity is frequently altered through dilution, substitution, contamination, and adulteration. Sugars, talc, starch, and carbonates represent the principal diluents of cocaine, while phenacetin, levamisole, caffeine, and lidocaine are its major adulterants in Europe. Levamisole is used because it is an odorless powder, with physical properties similar to cocaine, and it has reasonable cost and availability, being widely used in veterinary medicine. For this study, we analyzed 88 cocaine samples. The seized cocaine analyzed showed an average purity of 55% and the most frequent adulterants identified were: levamisole (31.8%), caffeine (6.8%), lidocaine (2.3%), acetaminophen (2.3%), and phenacetin (1.1%). Our aim is the study of the presence of levamisole, over other adulterants in seized cocaine samples, due to its recognized human toxicity. The chronic use of levamisole-adulterated cocaine represents a serious public health issue because it may be responsible for side-effects such as dermal vasculopathy, leukoencephalopathy, leukopenia, agranulocytosis, pulmonary hemorrhage, multiple emboli, and several other effects. Moreover, aminorex can cause idiopathic pulmonary hypertension, presenting another harmful and mostly lethal side-effect from cocaine cut with levamisole. In conclusion, levamisole determination should be performed in routine toxicological analysis in deaths due to cocaine use.